2014
DOI: 10.1111/tbed.12204
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Analysis of Influenza A Infection in Cambodian Pigs and Recommendations for Surveillance Strategies

Abstract: SummaryThis study analysed the available data of seroprevalence to human influenza viruses in pigs in Cambodia using generalized linear mixed models in order to improve understanding of factors underlying the spread of human influenza viruses in Cambodian pigs. The associations between seroprevalence against seasonal H1N1 influenza virus in pigs and the population density of humans and pigs were not significant. However, a positive association between anti-H3 antibodies in pigs and the human population density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Other studies have shown that TR H3N2 has potential for bidirectional transmission between humans and pigs and that five core genes from the TR internal gene cassette are carried by H1N1pdm09 (Garten et al, 2009). The TR H3N2 detected among pigs in this study has not previously been reported in Cambodia, but antibodies in pigs against human H3N2 have been described Netrabukkana et al, 2014). Interestingly, in the study by Rith et al (2013), all sera originating from pigs in Kampot province (n = 19) were seronegative to H1N1 and H3N2.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Other studies have shown that TR H3N2 has potential for bidirectional transmission between humans and pigs and that five core genes from the TR internal gene cassette are carried by H1N1pdm09 (Garten et al, 2009). The TR H3N2 detected among pigs in this study has not previously been reported in Cambodia, but antibodies in pigs against human H3N2 have been described Netrabukkana et al, 2014). Interestingly, in the study by Rith et al (2013), all sera originating from pigs in Kampot province (n = 19) were seronegative to H1N1 and H3N2.…”
Section: Discussioncontrasting
confidence: 48%
“…Since 2004, Cambodia has reported 44 poultry outbreaks and 56 human cases of HP H5N1, which has led to increased active and passive influenza surveillance (World Health Organization, , OIE (World Health Organization For Animal Health, ). The active surveillance in livestock has mainly targeted detection of HP H5N1 in poultry and the surrounding environment in live bird markets (Fournié et al., ; Horm et al., , ) and serological detection of human H1N1 and H2N3 antibodies in pigs (Rith et al., ; Netrabukkana et al., ). The surveillance methods used are applicable in Cambodia since influenza vaccination is prohibited in poultry and negligible in pigs (Theary et al., ; Netrabukkana et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cambodia, while there are in uenza [21,22] and Japanese Encephalitis [23,24] studies in pigs and wildlife zoonoses [25] studies, which are collaborations between international organisations and government-funded research institutes, there is a general lack of published scienti c information on animal disease surveillance in large ruminants and limited studies conducted on transboundary livestock movements. Several reports were available on the FMD National Surveillance and Control Program implemented by NAHPRI-GDAHP.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Vietnam, one of the highest pig producing countries in Southeast Asia (SEA), a high sero-prevalence of H1N1pdm09 was found (Baudon et al, 2015). Other countries in southeast Asia such as Malaysia and Cambodia reported serologic evidence of SIV subtype H1N1 and H3N2 circulating in the swine population prior the introduction of H1N1pdm09 (Suriya et al, 2008;Netrabukkana et al, 2015). Myanmar and Laos have no data on SIVs (Trevennec et al, 2011).…”
Section: Discussionmentioning
confidence: 99%